2021
DOI: 10.1080/16506073.2021.1907614
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel associations of daily skill use and effectiveness with anxiety, depression, and stress in a transdiagnostic sample undergoing dialectical behavior therapy skills training

Abstract: Dialectical Behavior Therapy (DBT) is effective at treating disorders of emotion dysregulation. However, it is unclear which mechanisms contribute to these effects. The aim of this study was to characterize the within-person associations of two theoretically relevant mechanisims of change, skill use and skill effectiveness, with anxiety, stress, and depression. Participants (n = 19, Mage = 31.8, 68% female) with a primary anxiety or depressive disorder completed daily reports (N = 1344) of DBT skill use, perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
5
8
0
3
Order By: Relevance
“…Patients used skills more frequently in the UP, replicating findings of other CBTs (Southward et al, 2022 ), and extending them by further demonstrating growth in the size of patients’ skill repertoires. These increases suggest that more time in treatment helps patients more regularly implement their skills when needed and grow their skill repertoires.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Patients used skills more frequently in the UP, replicating findings of other CBTs (Southward et al, 2022 ), and extending them by further demonstrating growth in the size of patients’ skill repertoires. These increases suggest that more time in treatment helps patients more regularly implement their skills when needed and grow their skill repertoires.…”
Section: Discussionsupporting
confidence: 76%
“…Although no researchers to our knowledge have assessed skill quantity in the UP, preliminary evidence of its effects have been demonstrated in other CBTs (Southward et al, 2021 ). For example, patients with mood and anxiety disorders in dialectical behavior therapy skills training used more skills on days they experienced more intense anxiety and depression, which predicted next‐day decreases in anxiety and depression (Southward et al, 2022 ). Because loneliness encompasses cognitive appraisals of relationships that can be influenced by a variety of behaviors, using a wider variety of skills may be necessary to promote decreases in loneliness.…”
Section: Up Skills As a Candidate Mechanism Of Change For Lonelinessmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, improvements in the quality of patients' cognitive skills were associated with reductions in depressive symptoms across cognitive therapy for depression (Adler et al, 2015) and predicted subsequent reductions in depressive symptoms in internet-delivered CBT for depression (Forand et al, 2018). Southward, Eberle, et al (2021) tested the effectiveness of patients' skill use among patients in Dialectical Behavior Therapy skills training. In this study, greater daily skill effectiveness was related to less intense daily anxiety and depression.…”
Section: Quality and Effectiveness Of Skill Usementioning
confidence: 99%
“…It is possible that adolescents participating in a health intervention targeting improved emotion regulation may not only increase the overall frequency of emotion regulation skill use, but also broaden the range of emotion regulation strategies within their repertoire. This has been demonstrated to occur in intervention studies with adults and was found to improve mental health (Grommisch et al, 2020;Southward et al, 2022). Findings have not yet been extended to an adolescent sample.…”
mentioning
confidence: 97%